UMPSA and GUET China sign strategic agreement to lead regional smart technology collaboration - Nor Fadzillah, Zulkipli (UMPSA, 2025)
KUALA LUMPUR, 10 April 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and Guilin University of Electronic Technology (GUET), China, held a memorandum of agreement (MoA) exchange ceremony, marking the beginning of a collaboration in spatiotemporal intelligent interconnection information technology research between the two institutions.